Precariousness and social conflict: To a renewal of the sociological perspective ? - Beroud, Sophie; Bouffartigue, Paul (Cuadernos de Relaciones Laborales, 2013)
Increasing precariousness among workers is closely associated with trade unionism contemporary weakness. But this process also open new possibilities for social resistance and - union’s form and repertoire of actions recomposition. To identify these we need to revisit wage labor history and different types of responses to reduce insecurity. It seems particularly interesting to examine the stabilization dynamic of wage and the claims for unconstrained mobility. This historically detour helps to identify the truly new dimension in the process of contemporary insecurity and question how trade unions are reacting.